2004
DOI: 10.1111/j.0742-2822.2004.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversion of the Inferior Vena Cava Following Repair of Atrial Septal Defect Causing Hypoxemia

Abstract: Atrial septal defects (ASDs) are a common congenital abnormality, and operative repair is a routine, safe procedure. Diversion of the inferior vena cava (IVC) into the left atrium is an unusual complication following ASD closure. We report a case that illustrates the problem created by this right-to-left shunt. A middle-aged woman underwent ASD repair. She developed hypoxemia postoperatively. A transthoracic echocardiogram confirmed a right-to-left shunt, found only with agitated saline injected into the femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 5 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…The current treatment of choice would have been another surgical repair [1][2][3]. We describe the first case in which a connection between the IVC and the LA was closed percutaneously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current treatment of choice would have been another surgical repair [1][2][3]. We describe the first case in which a connection between the IVC and the LA was closed percutaneously.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few cases known in which drainage of the IVC into the LA after surgical repair of an inferior ASD has occurred [1][2][3][4]. An explanation is that a prominent Eustachian valve was unintentionally included into closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Reported factors associated with this complication include a large secundum defect or sinus venosus defect, and anomalous pulmonary return into the RA. (4) In our case we observed that the inferior rim of the defect was not included in the first surgical closure. In addition; there was a scar tissue covering the upper part of the IVC on the RA surface so we believe that there was partial diversion of the IVC at first and by healing process complete diversion of the cava occurred gradually.…”
Section: Discussionmentioning
confidence: 62%
“…The symptoms of this complication generally appear soon after surgery when the patient becomes cyanotic and hypoxic; however, some factors such as the relief of pulmonary venous congestion and right ventricular strain by the correction of the left-to-right shunt, the occurrence of only partial diversion of the IVC flow to the LA, and the occurrence of stenosis of the IVC, with collaterals draining to the SVC through an azygos vein may contribute to the appearance of the symptoms of this complication later in life (3) . Reported factors associated with this complication include a large secundum defect or sinus venosus defect, and anomalous pulmonary return into the RA (4) . Cannulation of the IVC and SVC through the auricle of the right atrium may play a role in increasing the risk of diversion of the IVC into the LA, especially in IVC type ASD.…”
Section: Discussionmentioning
confidence: 99%